Assessing Lipid Nanoparticle Protein Corona Formation and Cytocompatibility - Rand Abdulrahman; Huda Ibrahem; Amna Mahmood; Kevin Edward Treacher; Robin Bruno Capomaccio; Catherine Vasey; Yvonne Perrie; Zahra Rattray (University of Huddersfield Press, 2023)
Lipid nanoparticles(LNPs) represent an emerging new modality for mRNA delivery. Following administration and interaction with blood constituents, LNPs form a corona complex consisting of proteins adsorbed on the surface altering their stability, biological identity, and fate. Cytocompatibility of the LNPs is an important factor when considering their safety efficacy in delivering the encapsulated drug dose, lipid choice and the specific target cells. The aim of this study was to investigate the changes in LNP physical parameters in physiologically-relevant media. Key attributes such as particle size, polydispersity index and zeta-potential were measured using Dynamic Light Scattering (DLS) and Nanoparticle Tracking Analysis (NTA). Cytocompatibility was assessed via CellTiter-Glo® assay. Following 24-hour incubation of LNPs with Bovine Serum Albumin (BSA), the LNP z-average increased from 92.4 (± 49.0) nm to 131.4 (± 64.9) nm indicating interaction between LNPs and BSA. A decrease in percentage cell viability was demonstrated with increased lipid concentration for MCF-7 and A549 cell lines. This work shows changes in LNP physicochemical properties in the presence of protein and biologically relevant conditions consistent with protein surface adsorption. The cytocompatibility of LNPs can be associated with the type of lipids used in the synthesis of LNPs.